PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL ANIMASI PADA MATERI PERISTIWA KEBANGSAAN SEPUTAR PROKLAMASI KEMERDEKAAN DALAM MUATAN IPS DI KELAS V SD - Nur Pajrina, Leila (STKIP Subang, 2021)
The research aims to develop learning media in the form of animation video for grade V elementary school, especially the material on the incident of proclamation, to describe validity of learning media, to know response of user. The research used the method research R&D with ADDIE model. The results of research as follow : (1) the results of the validity test of the instructional media obtained 97,91% with the very good qualification, (2) the results of the validity test of the instructional material obtained 94,44% with the very good qualification, (3) the results of the instructional language obtained 93,75% with the very good qualification, (4) the results of individual trial obtained 93,33% with the very good qualification, (5) the results of small group trial obtained 90,62% with very good qualification. Thus, the audio visual animation media is suitable to use in process of learning.